2018
DOI: 10.1371/journal.pone.0203457
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the initial experience of hospitalisation to an acute psychiatric ward

Abstract: BackgroundPatient-reported satisfaction with inpatient psychiatric services, within the first few days of admission, is related to positive future outcomes. Despite its predictive value, little is known about this initial experience and what underlies these appraisals. The aim of this study was to qualitatively explore the initial experience of being admitted to an inpatient psychiatric ward.MethodsSemi-structured interviews were conducted with 61 recently admitted patients across five psychiatric hospitals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 31 publications
(37 reference statements)
1
21
0
10
Order By: Relevance
“…While definitions remain unclear as to what makes activities meaningful, the impact of limiting access to such activities has been demonstrated, with evidence denoting a link between the insufficient access to a range of activities and the reported high levels of boredom that are experienced by service users on acute mental health wards (Folke et al, 2018;Lindgren, Aminoff, & Graneheim, 2015;Newell, Harries, & Ayers, 2012;Wood & Alsawy, 2016). High levels of boredom have been found to negatively affect the service user experience (Chevalier, Ntala, Fung, Priebe, & Bird, 2018) and to negatively impact on the ward environment (Akther et al, 2019). This links to the emerging evidence suggesting that engagement in activity is beneficial to patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…While definitions remain unclear as to what makes activities meaningful, the impact of limiting access to such activities has been demonstrated, with evidence denoting a link between the insufficient access to a range of activities and the reported high levels of boredom that are experienced by service users on acute mental health wards (Folke et al, 2018;Lindgren, Aminoff, & Graneheim, 2015;Newell, Harries, & Ayers, 2012;Wood & Alsawy, 2016). High levels of boredom have been found to negatively affect the service user experience (Chevalier, Ntala, Fung, Priebe, & Bird, 2018) and to negatively impact on the ward environment (Akther et al, 2019). This links to the emerging evidence suggesting that engagement in activity is beneficial to patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study by Chevalier et al (), it was reported that the sense of not knowing what was happening on the ward and a lack of communication contributed to the overall negative experience of consumers who were receiving care for a mental illness. Participants in that study also reported a perceived divide between themselves and nursing staff.…”
Section: Discussionmentioning
confidence: 98%
“…Admission to an acute inpatient mental health unit has been reported to be a difficult time for consumers. In a study by Chevalier et al (), participants identified that not knowing what to expect, confusion and chaos on the ward and a lack of communication between staff and consumers contributed to their negative admission experience.…”
Section: Introductionmentioning
confidence: 99%
“…This sometimes ends with compulsory psychiatric hospitalization, which has been associated with adverse patient outcomes. 143 , 144 Possibilities to reduce potentially detrimental psychiatric hospitalization could include preventative monitoring program psychoeducation comprising accurate risk assessment and preparation of 24-hour crisis intervention programs to provide immediate psychiatric support and treatment. The former was associated with a host of better patient outcomes and experiences, including lower levels of perceived coercion and distress and higher levels of optimism.…”
Section: Responsementioning
confidence: 99%